RESERVOIR CHARACTERIZATION USING SCALED QP AND QS AT POSEIDON FIELD, BROWSE BASIN - Nuzul Cahyani Amalia; Ida Herawati (JGE (Jurnal Geofisika Eksplorasi), 2026)
Reservoir characterization is a critical component of hydrocarbon exploration and development. Seismic wave attenuation, which is closely linked to the physical properties of rocks, has emerged as an effective tool for this purpose. The Scaled Qp and Qs (SQp and SQs) methods represent advanced attenuation-based technique capable of discriminating lithology and fluid content through analysis of P-wave and S-wave attenuation. This study applies SQp and SQs attributes to characterize lithology and fluid distribution within the Plover Formation of the Poseidon Field, using 3D partial angle stack seismic data and well logs from three wells: Kronos-1, Poseidon-1, and Poseidon-2. Crossplot analysis indicate that low SQp values (0.02–0.2) are associated with sandstone, whereas higher SQp values (0.2–0.7) correspond to shale. In terms of fluid discrimination, high SQs values (0.55–0.7) identify gas-bearing zones, while lower SQs values (0.4–0.55) indicate brine-saturated interval. SQp and SQs volumes derived from simultaneous inversion reveal that gas-saturated sandstone reservoirs — characterized by low SQp and high SQs — are distributed along a southwest to northeast trend, consistent with the location of all three wells. These results demonstrate that SQp and SQs attributes effectively distinguish reservoir from non-reservoir lithology and delineate hydrocarbon-bearing zones, providing a reliable attenuation-based workflow for reservoir characterization in similar geological settings.